Effects of dexamethasone on the growth of cultured rabbit articular chondrocytes:relation with the nuclear glucocorticoid-receptor complex. Issue 2 (February 1987) - Hainque, B; Dominice, J; Jaffray, P; Ronot, X; Adolphe, M
Abstract : This study reports that dexamethasone at a high dose (10(-4) mol/l) induced slowing of the in vitro proliferation of rabbit articular chondrocytes in both monolayer and clonal culture. This effect is consistent with an inhibition of DNA and RNA synthesis and was characterised by an accumulation of cells in the G0G1 phase of the cell cycle, as shown by flow cytometric analysis. Therefore we determined the extent of nuclear localisation of dexamethasone-receptor complexes. The results showed a discrepancy between 50% growth inhibitory dose (10(-4) mol/l) and the apparent affinity, KD (1.4 (SD 0.2) X 10(-9) mol/l). Thus the growth inhibition of rabbit articular chondrocytes by dexamethasone did not seem to be related exclusively to an interaction with the glucocorticoid-receptor complexes.